Hepatocyte Growth Factor Regulates Macrophage Transition to the M2 Phenotype and Promotes Murine Skeletal Muscle Regeneration - Choi, Wooshik; Lee, Jaeman; Lee, Junghun; Lee, Sang Hwan; Kim, Sunyoung (Frontiers in Physiology, 2019)
Hepatocyte growth factor (HGF) is well known for its role in the migration of embryonic muscle progenitors and the activation of adult muscle stem cells, yet its functions during the adult muscle regeneration process remain to be elucidated. In this study, we showed that HGF/c-met signaling was activated during muscle regeneration, and that among various infiltrated cells, the macrophage is the major cell type affected by HGF. Pharmacological inhibition of the c-met receptor by PHA-665752 increased the expression levels of pro-inflammatory (M1) macrophage markers such as IL-1β and iNOS while lowering those of pro-regenerative (M2) macrophage markers like IL-10 and TGF-β, resulting in compromised muscle repair. In Raw 264.7 cells, HGF decreased the RNA level of LPS-induced TNF-α, IL-1β, and iNOS while enhancing that of IL-10. HGF was also shown to increase the phosphorylation of AMPKα through CaMKKβ, thereby overcoming the effects of the LPS-induced deactivation of AMPKα. Transfection with specific siRNA to AMPKα diminished the effects of HGF on the LPS-induced gene expressions of M1 and M2 markers. Exogenous delivery of HGF through intramuscular injection of the HGF-expressing plasmid vector promoted the transition to M2 macrophage and facilitated muscle regeneration. Taken together, our findings suggested that HGF/c-met might play an important role in the transition of the macrophage during muscle repair, indicating the potential use of HGF as a basis for developing therapeutics for muscle degenerative diseases.